Switching mobile operators: Evidence about consumers' behavior from a longitudinal survey. (June 2019) - García-Mariñoso, Begoña; Suárez, David
Abstract: The rate at which consumers switch providers is a key indicator of the level of competition among mobile telephone operators. This paper uses a longitudinal survey of 4110 mobile users in Spain in 2015 and 2016 to analyze what drives consumers' decisions to switch mobile operators. After controlling for a number of individual characteristics, including gender, age, education level and employment status, switching was found to be significantly less common among satisfied customers and those whose mobile service was bundled with fixed services. Moreover, the more complex the bundle was, the lower the rate of switching was. Considerable consumer inertia was also found: inattentive consumers and those who had not switched previously were much less likely to switch. The implications of these results for regulators and operators are discussed. Highlights: Satisfaction was the main driver of mobile non-switching. Bundling significantly reduced switching especially bundles with more than 1 mobile. Consumer inattention hindered mobile switching. Past mobile switching increased subsequent mobile switching.